Optical microcavities enhance the exciton coherence length and eliminate vibronic coupling in J-aggregates - Spano, F C (The Journal of chemical physics, 2015)
The properties of polaritons in J-aggregate microcavities are explored using a Hamiltonian which treats exciton-vibrational coupling and exciton-photon coupling on equal footing. When the cavity mode is resonant with the lowest-energy (0-0) transition in the J-aggregate, two polaritons are formed, the lowest-energy polariton (LP) and its higher-energy partner (P1), separated by the Rabi splitting. Strong coupling between the material and cavity modes leads to a decoupling of the exciton and vibrational degrees of freedom and an overall reduction of disorder within the LP. Such effects lead to an expanded material coherence length in the LP which leads to enhanced radiative decay rates. Additional spectral signatures include an amplification of the 0-0 peak coincident with a reduction in the 0-1 peak in the photoluminescence spectrum. It is also shown that the same cavity photon responsible for the LP/P1 splitting causes comparable splittings in the higher vibronic bands due to additional resonances between vibrationally excited states in the electronic ground state manifold and higher energy vibronic excitons.